PENGARUH PEMAHAMAN SISTEM AKUNTANSI DAN SAK EMKM TERHADAP USAHA MIKRO KECIL DAN MENENGAH (UMKM) OTOMOTIF KECAMATAN KASIHAN - Mbadhi, Agnes; PD, Maria Magdalena; Isfaatun, Eliya; Sukmarani, Wendri (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
Accounting Information Systems are very useful as a basis for decision-making for companies and external parties. The Accounting Information System can provide a variety of important company accounting information and can determine the company's sustainability. This research aims to determine the influence of understanding the EMKM accounting system and SAK on automotive small and medium enterprises (UMKM) in Kasihan District, Bantul Regency, Yogyakarta Special Region. Using quantitative research methods with primary data from the Automotive MSME population in Kasihan District. The sample selection used the Non-Random Sampling Technique with a quota determined to be a research sample of 33 SMEs. Data analysis used the Multiple Linear Regression Analysis method with SPSS 20. The results of the study show that understanding of the accounting system influences the management of automotive SMEs. The results of simultaneous data analysis of the Understanding of the Accounting System and SAK EMKM have an effect on the Management of Automotive MSME. Meanwhile, SAK EMKM has no effect on MSME Management.